Optimalisasi Penyusunan Panduan Asuhan Keperawatan di Unit Hemato Onkologi - Vivin Ari S; Laode Abdul Rahman; Yuni Susiana Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to optimize the preparation of nursing care guidelines in the Hemato Oncology unit of RS X Bogor City. The method used in this research is a pilot project. The results showed that the majority of the ages were in the age range of 21-30 years, 85%, with the majority being female, as much as 80%. The competency level of nurses for pre-PK has the highest percentage at 40%. The length of work of nurses in the hemato-oncology unit is 2-5 years, as much as 60%. Respondents are implementing nurses as much as 95% and D3 education as much as 75%. The training qualification for implementing nurses that must be followed is BTCLS (Basic Trauma Cardiac Life Support) training. All nurses in the unit have attended as many as 95.24%. This research resulted in formulating an innovative nursing care guide in the Hematology-Oncology Unit. The focus was compiled because the preparation of nursing care guidelines at Hospital X Bogor City was not optimal, especially for cases in the Hematology-Oncology Unit. In conclusion, the nursing care guide becomes a guideline that will be used in determining care for patients who will bridge the nursing profession in preparing nursing care plans, especially in cases of hemato-oncology. Keywords: Integrated Collaboration, Nursing Care Guide